Atlas of PET-CT A Quick Guide to Image Interpretation - Fanti, Stefano (Springer Berlin Heidelberg, 2018)
This new atlas, the fourth of a successful series, is a completely revised and updated edition of a previously published FDG PET-CT atlas. In the past few years, considerable progress has been made in the field of PET-CT imaging, and this new edition takes full account of these recent developments. Furthermore, its educational mission has been broadened: beyond serving as a straightforward guide to FDG PET-CT imaging it now encompasses the integrative use of contrast-enhanced CT and MRI. The new edition also includes non-oncological indications for FDG PET-CT. The atlas aims to help imaging practitioners to recognize physiological and benign pathological FDG uptake and illustrates in a case-based, practical manner the PET-CT appearances of all the major tumors and infectious, inflammatory, and neurodegenerative disorders. The main clinical applications are covered, and learning points and pitfalls are clearly articulated. The consistent, user-friendly format facilitates image interpretation and allows rapid review of key information needed for FDG PET-CT imaging.